(3EOGQI GdUas - (3Jhb, eMj GdOjfs ((3HjQhJs c)
(3JYJHQ GdEOGQI GdUajI ef GdbVGjG GdJQHhjI GdgGeI dCfgG YfUQ CSGSj aj aGYdjI GdJOQjS hfLGM GdYedjI GdJYdejI (B- (3GdJYdjejI aj JMbjb CgOGagG GdNGUI(B. (3hCKHJJ GdOQGSGJ Cf GdEOGQI GdUajI GdaYGdI hGdfGLMI JQJHW HEQJaGY JMUjd GdWdHI HTcd eDcO hJfHY CgejI GdEOGQI GdUajI ef YdGbJgG GdeHGTQI HeTcdGJ GdEfVHGW aj GdUa hGdeOQSI(B. (3Je JYQja GdEOGQI GdUajI Ydi CfgG EjLGO HjFI JYde (B((3ELJeGYjI heGOjI(B) (3EjLGHjI, efJLI hedGFeI dJYde GdWdHI hfehge ef NdGd GdESJNOGe GdCeKd dechfGJ hYfGUQ GdZQaI GdUajI dJMbjb GdCgOGa GdJYdjejI(B. (3Ke PcQJ YhGed gPg GdEOGQI GdUajI, ef MjK GdbhGfjf hGdELQGAGJ, GdJONd dCZQGV GdVHW, GdYdGbI Hjf GdeYde hGdWGdH, Gdehba Ch GdJhLg GdPgfj(B. (3HYOgG Je GdJYQa Ydi CfeGW GdeYdejf aj GdZQaI GdUajI, GdfeW GdeJSdW, GdfeW GdLGRe, GdfeW GdeJaQL, hGdfeW GddGeHGdj(B. (3HGdEVGaI Edi Pdc Je YQV eHGOF GdEOGQI GdUajI GdeSJfOI Edi OQGSGJ ef LGeYI JcSGS, cVQhQI hVY hJWhjQ eLehYI ef GdbhGYO hGdELQGAGJ, JMOjO GdYhGbH aj MGd YOe GdEdJRGe HGdbhGYO, VQhQI GdJNWjW GdLjO ddecGf dJSgjd YedjI GdJYde, dESJNOGeGJ GdceHjhJQ aj GdZQaI GdUajI, VQhQI GdEYOGO GdLjO ddCSGHjY GdChdi ef HOA GdJOQjS, h VQhQI GdeMGaXI Ydi HjFI LjOI ddJYde(B. (3aVdG Yf Cfg Je HdhQI HjFI GdJYde dEOGQI UajI aYGdI, GdJj JYJeO Ydi KdGKI ehLgGJ QFjSjI(B: (3GdChdi, JTLjY EfTZGd GdWdHI aj GdCfTWI GdUajI Ydi CcHQ bOQ eecf(B. (3GdKGfjI, GdhbGjI hGdJMhW ef GdeTcdGJ hefY hbhYgG(B. (3hGdKGdKI gj GdJYGed eY GdeTcdGJ HMRe hQhjI hEfRGd GdYbhHGJ habG dEYJHGQGJ eMOOI heYjfI(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Class Management; Formation continue des enseignants; Gestion d$1 (Bune classes; Teachers in-service training; (3GOGQI GdUas; (3JOQjH GdeYdejfs